The Effect of Electronic Word of Mouth and Celebrity Endorsement on Customer Loyalty Through TikTok Application on Sasha Vitamin Products with Brand Image as a Mediation Variable in Mega Regency, Bekasi - Hartono, Melissa Eka Murti; Setyaningrum, Retno Purwani (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Along with the rapid development of digital technology, social media such as TikTok has become an important platform in modern marketing strategies, including in the beauty and hair care industry. Despite having advantages in halal content and certification, Sasha brand hair vitamins still lag behind its competitors in terms of customer loyalty. The purpose of this study was to analyze the effect of Electronic Word of Mouth (E-WOM) and Celebrity Endorsement on Customer Loyalty, with Brand Image as a mediating variable, through the use of the TikTok application on Sasha hair vitamin products in the Mega Regency area of ​​Bekasi Regency. This study uses a quantitative method, sampling using the lemeshow formula and a sample of 100 respondents was obtained. Data collected through questionnaires distributed using Google Form. Data management is carried out using Partial Least Square (PLS) through the Structural Equation Model (SEM) technique with the help of the SmartPLS version 4.1.1 program. The results of the analysis obtained are that electronic word of mouth has a significant effect on customer loyalty, celebrity endorsement does not have a significant effect on customer loyalty, brand image has a significant effect on customer loyalty, electronic word of mouth has a significant effect on brand image, celebrity endorsement has a significant effect on brand image. In addition, electronic word of mouth has a significant effect on mediating brand image on customer loyalty, and celebrity endorsement has a significant effect on mediating brand image on customer loyalty through the TikTok application on Sasha hair vitamin products in Mega Regency, Bekasi Regency.